The Efficacy of School Libraries in Fostering Student Literacy and Numeracy at SDN 11 Sungai Nyirih, Indonesia - Yasir Riady; Mas Hidayat; Melisa Arisanty; Majidah; Ahmad Jum'a Khatib Nur Al (IJLTP, 2025)
This study aims to evaluate the efficacy of school libraries in fostering numeracy literacy among students at SDN 11 Sungai Nyirih. Literacy and numeracy serve as crucial foundations for enhancing the quality of student learning at the primary school level. The employed research methodology is action research utilizing a qualitative approach. Data was collected through interviews, observations, and recording in the Education unit of the 11 Sungai Nyirih State Elementary School, involving various teachers, students, and library managers. The study's findings indicate that school libraries are crucial for learning support by offering pertinent materials, conducting literacy activities like shared reading, and facilitating interactive numeracy training. Nonetheless, challenges such as restricted book collections, inadequate infrastructure, and limited access to technology hinder the efficacy of libraries in facilitating learning. This study suggests that enhanced administration, increased acquisition of instructional resources, and technological integration can enable school libraries to significantly improve student reading and numeracy quality. The ideas propose the creation of enhanced reading and numeracy programs, including training for library administrators to address issues in the digital age.